Exploring distance learning in rural private schools in the Philippines: Challenges, coping mechanisms, and model development - Escala, Audrey Mae L.; Niez, Roland A.; Tancinco, Noel P.; Ralar, Tyron James T.; Paz, Pearl Irish V. De; Magno, Jelyn M.; Bulasito, Johnalisa L.; Gervacio, Aina P.; Plecerda, Lanie P.; Sereño, Remeca M.; Gelizon, Mary Joy B. (Edelweiss Applied Science and Technology, 2024)
The COVID-19 pandemic brought significant changes to the educational landscape, impacting not only public schools but also private learning institutions. This study explores the experiences of private schools at the administrative and faculty levels, focusing on the challenges encountered and the coping mechanisms employed in implementing distance learning. A descriptive phenomenology research design was used, emphasizing the subjective experiences of private school administrators and teachers. The researchers applied phenomenology to understand the core structure of their experiences in remote teaching and learning, with the goal of informing best practices and guiding potential changes in policies, theories, or responses to distance learning.Private schools faced a range of challenges due to this sudden shift, including insufficient professional preparation for teachers and inadequate technological infrastructure, both of which significantly affected the quality of distance learning. Despite these constraints, school leaders and teachers collaborated to propose strategies for mitigating the impact of these challenges. Key recommendations include prioritizing internet connectivity as a basic project for IT infrastructure with the support of school personnel and community leaders. Additional strategies involve offering diverse teaching modalities, conducting learner assessments, establishing effective communication and feedback systems, practicing efficient time management, fostering positive relationships, demonstrating professional integrity, advocating for ongoing training and simplified instruction, and recognizing the unique value of each learner within their academic environment.